A Thermodynamic Approach to Effective Stresses in Unsaturated Soils Incorporating the Concept of Partial Pore Deformations. Issue 5 (27th May 2014) - Dangla, Patrick; Pereira, Jean-Michel
Abstract : The thermodynamical analysis presented here follows from the work of Coussy et al., who proposed a thermodynamically consistent model for unsaturated soils that is based on a Bishop‐like effective stress to describe the stress–strain relationship while the water saturation (or the capillary pressure) is involved in a saturation‐induced hardening in addition to the mechanical hardening. We extended this model to include the effect of interfaces in the mechanical behavior and we showed that the Bishop‐like stresses involved in the elastic and plastic responses respectively can take different expressions. The Modified Cam–Clay model used for saturated soils is extended to unsaturated soils through the use of these Bishop‐like stresses. This model is compared to some experimental results reported from the literature.